The Use of Banten Folklore and Vocabulary Mastery on The Students’ Narrative Text Writing Skill - Suryadi Suryadi; Achmad Hufad; Suroso Mukti Leksono (Universitas Cokroaminoto Palopo, 2022)
The purpose of this study was to determine the influence of Banten folklore and vocabulary mastery on students' ability to write narrative texts. This quasi-experimental research used a two-by-two non-equivalent control group design with a factorial layout in four parallel classes, namely class XI IPS 1, XI IPS 2, XI IPS 3, XI IPS 4, and XI IPS 5. Pretest and posttest activities were used to collect data on learning outcomes. The sample consists of 80 students chosen at random according to the condition and purpose of the study. The findings indicate a substantial difference between the experimental and control groups on the posttest. The FO value is 5.225, and the Sig. value is 0.025 < 0.05. As a result, it demonstrates that the null hypothesis was rejected while the research hypothesis was supported. This also implies a distinction between the interaction impact of Banten folklore and vocabulary knowledge on students' ability to write narrative texts.